BSE risk, science, and governance - Van Zwanenberg, Patrick; Millstone, Erik. (Oxford : Oxford University Press, 2005)
This text provides an analysis of the BSE crisis and how policy-making processes were managed, and of how and why they culminated in catastrophic failure.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bovine spongiform encephalopathy -- Prevention -- Government policy -- Great Britain